2018
DOI: 10.1111/jace.15890
|View full text |Cite
|
Sign up to set email alerts
|

Greatly enhanced photocurrent in inorganic perovskite [KNbO3]0.9[BaNi0.5Nb0.5O3‐σ]0.1 ferroelectric thin‐film solar cell

Abstract: Inorganic perovskite [KNbO3]0.9[BaNi0.5Nb0.5O3‐σ]0.1 (KBNNO) ferroelectric thin films with narrow band gap (1.83 eV) and high room‐temperature remnant polarization (Pr = 0.54 μC/cm2) was grown successfully on the Pt(111)/Ti/SiO2/Si(100) substrates by pulsed laser deposition. Ferroelectric solar cells with a basic structure of ITO/KBNNO/Pt were further prepared based on these thin films, which exhibited obvious external‐poling dependent photovoltaic effects. When the devices were negatively poled, the short‐cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Thus, the across‐the‐band‐gap excitation was a transition from Ni 3 d to Nb 4 d states. LDA+ U calculations gave the band gap of 1.8 eV which was in good agreement with the values measured for this material in several experimental studies in the range from 1.4 to 2.0 eV . It was also found that the band gap and absorption features are quite sensitive to the composition and the preparation method, indicating that the Ni electronic structure is quite flexible and can be readily modified by small changes in the cation and oxygen stoichiometry.…”
Section: Introductionsupporting
confidence: 86%
“…Thus, the across‐the‐band‐gap excitation was a transition from Ni 3 d to Nb 4 d states. LDA+ U calculations gave the band gap of 1.8 eV which was in good agreement with the values measured for this material in several experimental studies in the range from 1.4 to 2.0 eV . It was also found that the band gap and absorption features are quite sensitive to the composition and the preparation method, indicating that the Ni electronic structure is quite flexible and can be readily modified by small changes in the cation and oxygen stoichiometry.…”
Section: Introductionsupporting
confidence: 86%
“…In FE-based self-driven photodetectors, two mechanisms are usually responsible for separation and acceleration of photo-generated carriers. One is the depolarization electric field present across bulk FEs and the other is the Schottky barrier formed at interfaces between FEs and metal electrodes. , Recent works have demonstrated that FE-based photodetector device performance can be improved by coupling the PV and pyroelectric effects of the FE materials. , However, the responsivity ( R ) of this type of photodetector remains quite low, and the detectors work only in certain environments. Thus, there is an urgent need to improve the performance of FE-based photodetectors.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of poling on the performance and charge separation in such devices is discussed. [ 67 ]…”
Section: Part Ii: Other Laser Methods For Pscsmentioning
confidence: 99%
“…The influence of poling on the performance and charge separation in such devices is discussed. [67] PSCs based on combining a [KNbO 3 ](0.9)[BaCo 0.5 Nb 0 . 5 O 3−δ ] (0.1) perovskite oxide as sensitizer with well-aligned TiO 2 Reproduced with permission.…”
Section: Figure 9 Clearly Illustrates the Interdependency Between Cry...mentioning
confidence: 99%